2021
DOI: 10.3390/insects12100877
|View full text |Cite
|
Sign up to set email alerts
|

Successful Eradication of the Asian Longhorn Beetle, Anoplophora glabripennis, from North-Eastern Italy: Protocol, Techniques and Results

Abstract: The Asian Longhorn Beetle (ALB), Anoplophora glabripennis (Coleoptera: Cerambycidae), is an important and extremely polyphagous wood-boring beetle native to Asia. In the 1990s, ALB was accidentally introduced into North America and Europe. In 2009, a large ALB infestation was found in the Veneto Region (north-eastern Italy), in the municipality of Cornuda (Treviso province). Eradication actions were immediately undertaken, based on delimitation of infested and buffer zones, tree visual inspections, felling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Many management strategies have been widely used to monitor and control A. glabripennis , including the eradication of infested trees [ 12 ], chemical insecticide treatment [ 39 , 40 ], and biological control of natural enemies [ 41 , 42 , 43 ]. However, eradication programs have proven to be one of the most effective methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many management strategies have been widely used to monitor and control A. glabripennis , including the eradication of infested trees [ 12 ], chemical insecticide treatment [ 39 , 40 ], and biological control of natural enemies [ 41 , 42 , 43 ]. However, eradication programs have proven to be one of the most effective methods.…”
Section: Discussionmentioning
confidence: 99%
“…To accurately detect and estimate its population density, a great deal of research has indicated that olfactory signals play an important role in the intra- and interspecific communication of A. glabripennis adults [ 6 , 7 , 9 ]. Several sex pheromones and host kairomones have been identified, and single pheromones, as well as a combination of both semiochemical types, have been used as tools for detection and monitoring in A. glabripennis adults in the field [ 10 , 11 ], but few beetles were captured by the dozens of traps at Cornuda, Italy [ 12 ], and Paddock wood, UK [ 13 ]. Xu and Teale [ 9 ] also suggested that semiochemical-based traps baited with a mixture of host kairomones (plant volatile organic compounds) and sex pheromones have still not reached operational efficacy for A. glabripennis adults in field bioassays.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive species of scolytid beetles with high aggressivity are capable of suppressing their host plant species throughout whole regions within a few years (Cullingham et al., 2011; Montecchio et al., 2016). Such a loss of production (and also costs of related plant protection measures) results in high financial damage and negative social impacts (Marchioro & Faccoli, 2021; Montecchio et al., 2016; Valenta et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, it took 11 years to completely eradicate A . glabripennis in the Cornuda region of northeast Italy [ 11 ]. However, it is difficult to eradicate A .…”
Section: Introductionmentioning
confidence: 99%